Financial empowerment, digital financial literacy, and family support in transforming migrant remittances into productive business capital - Asep Hendriana; Indri Guslina; Iqbal (Universitas Widya Mataram, 2026)
Financial empowerment, digital financial literacy, and family support in transforming migrant remittances into productive business capital Previous studies have rarely integrated financial empowerment, digital financial literacy, and family support in explaining productive remittance transformation among migrant households. This study aims to analyze the influence of financial empowerment, migrant digital financial literacy, and family support on the transformation of remittances into productive business capital among Indonesian migrant worker households. The study also examines the mediating role of family support in encouraging business-oriented remittance allocation and sustainable economic activities. A quantitative approach was employed using Partial Least Square–Structural Equation Modeling (PLS-SEM) through SmartPLS software. Data were collected from 111 Indonesian migrant worker households using purposive sampling techniques. The findings reveal that financial empowerment significantly affects both family support and productive remittance transformation. Family support also demonstrates a positive influence on entrepreneurial investment and productive economic activities. Meanwhile, migrant digital financial literacy shows weak and insignificant effects on both family support and productive remittance transformation. The study confirms that financial empowerment and family support are the dominant factors encouraging productive financial behavior among migrant households. Furthermore, family support partially mediates the relationship between financial empowerment and productive remittance transformation. These findings imply that financial empowerment programs and family-based financial education should be strengthened to support sustainable entrepreneurship and household economic resilience.